KINEMATIC DESIGN AS A TOOL IMPROVEMENT OF NAVAL MINES SEARCH - AFTANAZIV, IVAN; STROGHAN, ORYSIA; SHEVCHUK, LILIA; STRUTYNSKA, LESIA (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The issue of demining sea raids and ports, which is relevant for Europe during the period of active deployment of military confrontations on its territory, is considered. It is proposed to expand the search capabilities of trawler boats by adding auxiliary search vessels to them. This increases the effective search area by one and a half to two times, reducing by 25-30% fuel consumption for search passages of floating vehicles. The optimal trajectory of search movements of floating vehicles along the Archimedean spiral and the method of determining the coordinates of mines by means of kinematic design are proposed. The movement of search vessels along an Archimedean spiral is recommended due to the absence of sharp turns and reciprocating movements in such a trajectory, which are undesirable for the search movements of trawler boats. At the same time, the danger of having unlimited areas of the surface of the reservoir or the sea is also eliminated. As one of the most effective options for the disposal of mines, their detonation with warheads dropped from an aerial liquidator drone has been proposed. To clarify the coordinates of the location of anchor and bottom mines, it is proposed to use the kinematic design method. This technique provides for the formation of a base plane and the designation of a "picture" projection plane in the depth of the sea, on which the projecting rays will be projected. In this case, the wanted mine serves as a design object. The use of kinematic design techniques and an auxiliary floating search vessel to search for mines allows not only to carry out search operations without direct participation in the search of people, but also to increase the productivity and speed of search operations. In order to manage the movements of the search floats, to process the data provided by them about the detected mine, to specify the coordinates of the detected mine, a corresponding block diagram of the computer program is proposed. It was established that at speeds of 5÷5.5 knots of search movements of floating vessels, using the proposed search scheme, it is possible to survey up to 6 square kilometers of sea water area every hour. At the same time, it is possible to save up to 20 liters of valuable fuel during the survey of such an area due to the reduction of movements of the trawler boat.
Keywords: search; anchor and bottom mines; mine clearance; trawler boat; boat; additional floating vehicle; block diagram; calculation; coordinates; kinematic design